2022
DOI: 10.3389/fphar.2022.840320
|View full text |Cite
|
Sign up to set email alerts
|

A Loading Dose of Dexmedetomidine With Constant Infusion Inhibits Intraoperative Neuromonitoring During Thoracic Spinal Decompression Surgery: A Randomized Prospective Study

Abstract: Background: The effect of a bolus dose of dexmedetomidine on intraoperative neuromonitoring (IONM) parameters during spinal surgeries has been variably reported and remains a debated topic.Methods: A randomized, double-blinded, placebo-controlled study was performed to assess the effect of dexmedetomidine (1 μg/kg in 10 min) followed by a constant infusion rate on IONM during thoracic spinal decompression surgery (TSDS). A total of 165 patients were enrolled and randomized into three groups. One group received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19] Theoretically, dexmedetomidine could inhibit evoked potentials by increasing inhibitory synaptic transmission through activation of the descending noradrenergic system. 20 In a retrospective, observational study of 78 patients undergoing intracranial tumor resections, patients who received dexmedetomidine 0.5 mcg/kg bolus followed by 0.5 mcg/kg/h infusion had significantly higher TcMEP stimulation thresholds as compared with a control group, while SSEP stimulation thresholds were not significantly different between the 2 groups; 21 TcMEP amplitudes in both upper and lower extremities were also significantly lower among those who received dexmedetomidine. In a retrospective case-controlled study of 70 pediatric patients undergoing posterior spine surgery, dexmedetomidine infusion at 0.3 to 0.5 mcg/kg/h without bolus was associated with a statistically and clinically significant reduction in TcMEP amplitude from baseline.…”
Section: Dexmedetomidinementioning
confidence: 94%
See 2 more Smart Citations
“…[12][13][14][15][16][17][18][19] Theoretically, dexmedetomidine could inhibit evoked potentials by increasing inhibitory synaptic transmission through activation of the descending noradrenergic system. 20 In a retrospective, observational study of 78 patients undergoing intracranial tumor resections, patients who received dexmedetomidine 0.5 mcg/kg bolus followed by 0.5 mcg/kg/h infusion had significantly higher TcMEP stimulation thresholds as compared with a control group, while SSEP stimulation thresholds were not significantly different between the 2 groups; 21 TcMEP amplitudes in both upper and lower extremities were also significantly lower among those who received dexmedetomidine. In a retrospective case-controlled study of 70 pediatric patients undergoing posterior spine surgery, dexmedetomidine infusion at 0.3 to 0.5 mcg/kg/h without bolus was associated with a statistically and clinically significant reduction in TcMEP amplitude from baseline.…”
Section: Dexmedetomidinementioning
confidence: 94%
“…In a double-blinded RCT involving 160 patients undergoing thoracic spine surgery, participants were randomized to receive either dexmedetomidine 1 mcg/kg bolus followed by 0.5 mcg/kg/h infusion, dexmedetomidine 0.5 mcg/kg/h infusion without bolus, or placebo infusion. 20 The authors reported, through within-group analysis, a significant decrease in TcMEP and SSEP amplitudes and a significant increase in SSEP latencies for up to 25 minutes following the administration of dexmedetomidine bolus and infusion; this phenomenon was not observed in the placebo group or in the dexmedetomidine infusion only group. Taken together, dexmedetomidine, while apparently compatible with IONM at low-doses, may elicit a dose-dependent suppression of SSEP and TcMEP amplitudes at higher doses.…”
Section: Dexmedetomidinementioning
confidence: 95%
See 1 more Smart Citation
“…The reported effects on MEPs in adults are variable. However, a loading dose of 1 mcg/kg of dexmedetomidine inhibited the MEP amplitude, for up to 25 min, suggesting a Ce–response relationship 34 . Use of dexmedetomidine at a TCI of 0.3–0.6 ng/mL combined with propofol/remifentanil to a target BIS 40–60, allows measurable MEPs.…”
Section: Intravenous Anestheticsmentioning
confidence: 96%
“…However, a loading dose of 1 mcg/kg of dexmedetomidine inhibited the MEP amplitude, for up to 25 min, suggesting a Ce-response relationship. 34 Use of dexmedetomidine at a TCI of 0.3-0.6 ng/mL combined with propofol/remifentanil to a target BIS 40-60, allows measurable MEPs. However, dissenting study in children and adolescents demonstrated dexmedetomidine 0.3 and 0.5 mcg/kg/h (expected Ce 0.33-0.4 and 0.55-0.6 ng/mL) reduced MEPs by more than 50% in most measured muscle groups during spinal surgery.…”
Section: Dexmedetomidinementioning
confidence: 99%